Crocodile! crocodile! stories told around the world - Baumgartner, Barbara; Moffatt, Judith (London ; New York : Boston : D. Kindersley ; Distributed by Houghton Mifflin, 1994)
Engaging characters are brought to life in cheery cut-paper illustrations. This international collection of folk tales bring together six of Barbara Baumgartner's most successful performances on one volume. For the first time ever, this well-loved storyteller has written down her stories for school-age children to enjoy at home. Engaging characters-from the clever monkey who outwits a hungry crocodile, to a magical dragon that brings secret gifts to a kind young boy-are brought to life in Judith Moffatt's cheery cut-paper illustrations. Readers will also enjoy Bringing the Stories to Life with Stick Puppets, a special section at the end of the book. Following simple instructions for making their own puppets, children will learn how to act out the tales in the book. Through her animated stories, Barbara Baumgartner teaches young listeners the simple truths of folk tales and the wisdom that each imparts.
Crocodile! crocodile! -- Crocodile hunts for the monkey -- The squeaky old bed -- How the chipmunk got his stripes -- The grateful snake -- Sody saleratus.
5 - 9 years
71461
Keywords: Tales; Folklore